Trajectory estimation based on extended state observer with Fal-filter. (August 2015) - Lin, C-L; Hsieh, S-L; Lin, Y-P
Abstract: This paper intends to develop a target trajectory estimation algorithm with application to the ballistic target estimation in the terminal phase. The proposed design is based on the application of a second-order extended state observer (ESO) technique using target information acquired from the seeker to estimate the trajectory of manoeuverable ballistic targets. Satisfactory results have been received while applying the design in estimation of either two-dimenional or three-dimentional target evasive acceleration via computer simulation.